A comparison of the treatment effects of the Forsus Fatigue Resistance Device and the Twin Block appliance in patients with class II malocclusions - Hanoun A; Al-Jewair TS; Tabbaa S; Allaymouni MA; Preston CB (Dove Medical Press, 2014)
Abdulfatah Hanoun,1 Thikriat S Al-Jewair,1,2 Sawsan Tabbaa,1 Mhd Amer Allaymouni,1 Charles B Preston1 1Department of Orthodontics, School of Dental Medicine, State University of New York at Buffalo, NY, USA; 2College of Dentistry, University of Dammam, Saudi Arabia Objectives: We evaluated the skeletal and dentoalveolar effects of the Forsus Fatigue Resistance Device (FRD) and the Twin Block appliance (TB) in comparison with nontreated controls in the treatment of patients with class II division 1 malocclusion. Materials and methods: This retrospective study included three groups: TB (n=37; mean age, 11.2 years), FRD (n=30; mean age, 12.9 years), and controls (n=25; mean age, 12.6 years). Lateral cephalograms were evaluated at T1 (pretreatment) and at T2 (postappliance removal/equivalent time frame in controls). Cephalometric changes were evaluated using the Clark analysis, including 27 measurements. Results: Sagittal correction of class II malocclusion appeared to be mainly achieved by dentoalveolar changes in the FRD group. The TB was able to induce both skeletal and dentoalveolar changes. A favorable influence on facial convexity was achieved by both groups. Significant upper incisor retroclination occurred with the TB (-12.42°), whereas only -4° was observed in the FRD group. The lower incisors proclined more in the FRD group than the TB group. Incisor overjet reduction was 62% in the TB group versus 56% in the FRD group. Molar relation was corrected in both functional groups, resulting in a class I relation, although no change appeared in the control sample. Conclusion: Both appliances were effective in correcting the class II malocclusion. Both the FRD and the TB induced significant maxillary and mandibular dentoalveolar changes; skeletal changes were induced by TB but not FRD therapy. Keywords: orthodontics, cephalometry, class II malocclusion, functional appliances